2000
DOI: 10.1111/j.1151-2916.2000.tb01370.x
|View full text |Cite
|
Sign up to set email alerts
|

Pr3+/Er3+ Codoped Ge‐As‐Ga‐S Glasses as Dual‐Wavelength Fiber‐optic Amplifiers for 1.31 and 1.55 μm Windows

Abstract: Fluorescence emissions at both 1.31 and 1.55 m communication windows were observed from Pr 3؉ /Er 3؉ codoped Ge-AsGa-S glasses with a single wavelength pumping at 986 nm. The lifetime of the Er 3؉ : 4 I 11/2 level decreased as the Pr 3؉ concentration increased, and that of the Pr 3؉ : 1 G 4 level increased as the Er 3؉ concentration increased. Energy transfer from the Er 3؉ : 4 I 11/2 level to the Pr 3؉ : 1 G 4 level was responsible for emission of the 1.31 m fluorescence from the Pr 3؉ : 1 G 4 level. Ge-As-Ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 5 publications
1
7
0
1
Order By: Relevance
“…As will be explained later, 6 F 11/2 6 H 9/2 → 6 H 15/2 is the so‐called hypersensitive transition, 23 and most sensitive to the local symmetry of glass structure and thus to glass composition, while the transition probabilities in Pr 3+ ‐ and/or Nd 3+ ‐doped glasses were reported to depend largely on Ω 6 2 . Therefore we focus our attention on the electron transition of Dy 3+ : 6 F 11/2 6 H 9/2 → 6 H 15/2 in terms of Judd–Ofelt analysis, which was done using the calculated oscillator strengths of glasses 6,11,24 . Both calculated Judd–Ofelt intensity parameters Ω t=2,4,6 and fluorescence parameters, including effective radiative probability A eff and branching ratio β, were summarized in Table II.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As will be explained later, 6 F 11/2 6 H 9/2 → 6 H 15/2 is the so‐called hypersensitive transition, 23 and most sensitive to the local symmetry of glass structure and thus to glass composition, while the transition probabilities in Pr 3+ ‐ and/or Nd 3+ ‐doped glasses were reported to depend largely on Ω 6 2 . Therefore we focus our attention on the electron transition of Dy 3+ : 6 F 11/2 6 H 9/2 → 6 H 15/2 in terms of Judd–Ofelt analysis, which was done using the calculated oscillator strengths of glasses 6,11,24 . Both calculated Judd–Ofelt intensity parameters Ω t=2,4,6 and fluorescence parameters, including effective radiative probability A eff and branching ratio β, were summarized in Table II.…”
Section: Resultsmentioning
confidence: 99%
“…2 Therefore we focus our attention on the electron transition of Dy 31 : 6 F 11/2 6 H 9/2 -6 H 15/2 in terms of Judd-Ofelt analysis, which was done using the calculated oscillator strengths of glasses. 6,11,24 Both calculated Judd-Ofelt intensity parameters O t 5 2,4,6 and fluorescence parameters, including effective radiative probability A eff and branching ratio b, were summarized in Table II. Root-mean-square values of the fitting were in the range of 0.03-0.54 Â 10 À6 .…”
Section: August 2006mentioning
confidence: 99%
See 2 more Smart Citations
“…By replacing erbium with other rare earths such as Tm 3+ (Dai et al, 2010) or by co-doping with two rare earths (Tm 3+ /Ho 3+ , Pr 3+ /Er 3+ ) (Hewak, 1998;Park et al, 2000;Li et al, 2011), these materials could be promising candidates for the making of new laser sources working in the second atmospheric window ranged between 2 and 5 mm. This work will now be extended to selenide-based glass-ceramics, as Hubert et al (2013) have demonstrated that the same phenomenon can be observed in selenide-based glass-ceramics doped with Er 3+ .…”
Section: Enhancement Of Luminescencementioning
confidence: 99%